THE USE OF POWTOON ANIMATION LEARNING MEDIA ON STUDENTS' LEARNING MOTIVATION IN MATHEMATICS LEARNING - Hariananda, Dena Arimby; Kusmiyati, Kusmiyati (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
Mathematics is often considered an abstract subject because it involves concepts and symbols that can be difficult to understand directly or physically. However, using animated media such as Powtoon can help overcome this abstraction and make mathematics learning easier to understand and interesting by creating Powtoon-based animated learning media. Powtoon is a popular animation platform used to create presentations, promotional videos and other animated videos. With Powtoon, you can create attractive animations using various graphic elements, characters, and transition effects. In the research that has been done before, many studies say that to overcome boredom so that students are motivated while learning, the use of learning media is considered to make students easier to understand the material and make teaching and learning activities carried out more efficiently in implementing the learning process, especially in learning mathematics is by make interesting learning media. This study aims to analyze the use of Powtoon learning media on students' learning motivation in learning mathematics. This research is a qualitative research with descriptive analysis using library research. The data collected is the result of searching electronic journals through the library's Google Scholar. From the research results of 15 relevant articles, it shows that the Powtoon animation learning media is useful for increasing students' learning motivation in learning mathematics